MODERN ASPECTS OF ACUTE RESPIRATORY DISEASES TREATMENT IN CHILDREN: TOPICAL DRUGS IN RHINOPHARYNGITIS - A. S. Ostrovskaya; S. A. Ivanichkin ("Paediatrician" Publishers LLC, 2012)
The issues of acute respiratory diseases treatment in children, including the most common mistakes in management of such patients, unreasonable from the etiopathogenic point of view treatment with systemic antibacterial drugs and advantages of the topical therapy in arresting of the inflammatory process (in particular, of certain medical agents with topical effect) are discussed in this article. The authors review the most common otorhinolaryngological lesions in acute respiratory diseases. The problems of appropriate anaesthetic therapy and differentiated approach to the evaluation of sore throat in children of different age groups are emphasized.